2019
DOI: 10.1177/1029864919877564
|View full text |Cite
|
Sign up to set email alerts
|

Flow research in music contexts: A systematic literature review

Abstract: The purpose of this study was to review flow research in music contexts from 1975 until the first quarter of 2019. Specifically, frequencies/percentages were calculated for (a) output in five-year periods; (b) publication type; and (c) methodologies employed, including measurement instruments used. Content analyses were also conducted on topics covered. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, a total of 3,341 records were examined, with 95 studies even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 105 publications
1
39
0
Order By: Relevance
“…In recent years, interest in flow as another component of the broad term "motivation" within music contexts has increased tremendously (Tan and Sin, 2019). The concept of flow, originally described by Csikszentmihalyi, refers to a state which is characterized by the following components: (a) focusing exclusively on one's actions in the present, (b) a sense of control over one's actions, (c) experiencing the activity as pleasurable, (d) an absence of self-consciousness, as well as (e) a distorted perception of time, and (f) "the merging of action and awareness" (Nakamura and Csikszentmihalyi, 2005, p. 90).…”
Section: Motivation As An Umbrella Termmentioning
confidence: 99%
“…In recent years, interest in flow as another component of the broad term "motivation" within music contexts has increased tremendously (Tan and Sin, 2019). The concept of flow, originally described by Csikszentmihalyi, refers to a state which is characterized by the following components: (a) focusing exclusively on one's actions in the present, (b) a sense of control over one's actions, (c) experiencing the activity as pleasurable, (d) an absence of self-consciousness, as well as (e) a distorted perception of time, and (f) "the merging of action and awareness" (Nakamura and Csikszentmihalyi, 2005, p. 90).…”
Section: Motivation As An Umbrella Termmentioning
confidence: 99%
“…see [8, 15, 27, 47]. Previous research on flow state during improvisation was mostly done using interviews and observations [47]. In our case, a qualitative analysis of the values taken by the Focus rating, together with informal observations discussed with the performer, suggested that Focus was generally staying high during musical improvisation performance, and corresponded to a target for appropriate performance.…”
Section: Discussionmentioning
confidence: 67%
“…Another perspective developed in the literature consists in considering musical improvisation as a subjective state [6, 15, 26, 47]. This perspective revisits the involvement of brain networks of spontaneous, endogenous activity such as the default mode network [37], and considers the notion of flow state as central in the phenomenology of musical improvisation [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a form of optimal experience comprising a complex dance of cognitive, physiological and affective processes (Csikszentmihalyi, 1975(Csikszentmihalyi, , 2002. There has been increased research interest in flow and music (see Tan & Sin, 2019 for a systematic review). Flow experiences during improvisation are an important part of jazz culture and performance and are seen as integral to jazz musicians' competence as improvisers (Hytönen-Ng, 2013).…”
mentioning
confidence: 99%